Hubungan Motivasi, Modal Minimal, Literasi Keuangan, dan Minat Investasi Saham Taat Syariah - Rochman, Naufal Haidar; Sukartha, P D’yan Yaniartha (E-Jurnal Akuntansi; Vol 33 No 8 (2023), 2023)
Shares are one type of investment instrument that is most popular with the public, because the amount of capital issued is minimal and stock investment regulations are easy. Sharia compliant shares have better resilience compared to conventional shares. This research aims to determine the relationship between motivation, minimum capital and financial literacy in the context of sharia-compliant stock investment. A total of 118 students were observed as samples. A multiple linear regression approach was used for data analysis in this study. The research results show that motivation and financial literacy have a positive effect on the intention to invest in sharia shares, while minimum capital has no effect on the desire to invest in sharia shares. Keywords: Sharia Compliant Stocks; Motivation; Minimal Capital; Financial Literacy; Investment Interest